Seasonal changes in multiple indices of body composition in professional football players - Iga, J.; Scott, M.; George, K.; Drust, B. (International Journal of Sports Medicine, 2014)
We examined the seasonal variability of indicators of adiposity and generic and population-specific equations of estimating body fat in professional football players. Anthropometric data of 35 outfield players (age, 20±4 years; stature, 1.82±0.06 ; body mass 77.1±7.3 g) were collected over a playing season. There were a significant main effects for time for all indicators (p<0.001). Post hoc analysis revealed significant changes in body composition between July and mid-August (4SF-DW: 1.6 mm, p<0.001; 4SF-R: 2.4 mm, p=0.002; 5SF: 2.0 mm, p<0.002; 8SF: 3.8 mm, p=0.001; Reilly et al.: 0.4%, p=0.001; Durnin and Wormsley: 0.7%, p<0.001). Although all indicators were sensitive to detect small changes in body composition between training mesocycles, we advocate the use of the sum of 4 skinfolds by Reilly et al. to monitor changes in body composition in professional football players; if an estimate of percent body fat is required, the population-specific equation by Reilly et al. may be utilised.